The War in Ukraine and Academic Challenges - Ravna, Øyvind (Arctic Review on Law and Politics, 2022)
Russia’s military invasion of and war against Ukraine has caused enormous human suffering and material destruction. The situation also raises a number of academic and scholarly issues. This editorial describes the context for Arctic Review on Law and Politics’ plans for a special, thematic series devoted to these matters.